Biocatalytic Depolymerization of Poly(butylene-adipate-co-terephthalate) (PBAT) for Upcycling - Pyo, Sang Hyun ; 0000-0002-5037-2748; Ismail, Mohamed ; 0000-0003-3265-3500; Abouhmad, Adel Elsayed Attia; Englund Örn, Oliver; Hatti-Kaul, Rajni (2023 KSBB Spring Meeting and International Symposium, Seogwipo, Korea, Republic of, 2023-04-12 - 2023-04-15, 2023)
Transition to a circular plastic economy requires rethinking of the entire value chain from the raw materials and energy used for production, to material design, collection and recycling. Our focus has mainly been on polyesters as they span a wide scope of applications and properties ranging from durable to biodegradable. This presentation will highlight our work on designing and developing the biocatalytic process for depolymerization of a copolyester poly (butylene-adipate-co-terephthalate)(PBAT) for upcycling.